EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN HANDOUT PADA POKOK BAHASAN BESARAN DAN SATUAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMA NEGERI 1 GUBUG - Yi’laa Nurul Imama; Harto Nuroso; Nur Khoiri (Universitas PGRI Semarang, 2015)
This study was aimed to find out the effectiveness of cooperative script learning model with handout towards the students’ critical thinking ability. The design of the study was quasi experiment in the form of nonequivalent pretest-posttest control group design. This study was conducted in SMA N 1 Gubug on 1st -22th August 2015 with the population of an entire class of X classes in SMA N 1 Gubug. The sample of the study consisted of two classes taken with cluster random sampling technique that was class X-F as experimental class and the class X-G as the control class. The data collecting technique were test and documentation.Based on the data analysis, it was obtained the means of the pretest score of experimental class was 44,77 and the control class was 33,33. Meanwhile, the students’ average score of post-test in experimental class was 80,40 and the control class was 73,70. Based on the pre-test and post-test result from those classes, it showed that there was a significant effect between students’ independence and students’ outcome in experimental class compared with control class. The hypothesis testing used significant level 5% was obtained tcount = 2,83 dan ttable = 1,67. This result indicated that cooperative script learning model with handout is more effective to improve students’ critical thinking ability